CrowdMock : an approach for defining and evolving web augmentation requirements - Firmenich, Diego; Firmenich, Sergio Damián; Rivero, José Matías; Antonelli, Rubén Leandro; Rossi, Gustavo Héctor (2016)
Web Applications are accessed by millions of users with different needs, goals, concerns or preferences. Several well-known Web Applications provide personalized features, e.g. they recommend specific content to users by contemplating individual characteristics or requirements. However, since most Web Application cannot consider all users? requirements, many developers started to create their own mechanisms for adapting existing applications. One of the most popular techniques for third party applications adaptation is Web Augmentation, which is based on the alteration of its original user interface, generally by using scripts running at the client-side (e.g. the browser). In the context of Web Augmentation, two user roles have emerged: scripters who are those users able to create a new augmentation artefact, and end-users without programming skills, that just consume the artefacts that may satisfy totally or partially their needs. Scripters and end-users generally do not know each other and they have rarely a contact, beyond the fact that they use the same script repositories. When end-users cannot get their needs covered with existing artefacts, they claim for new ones by specifying their requirements (called Web Augmentation requirements) using textual descriptions, which are usually hard to interpret by scripters. Web Augmentation requirements are a very particular kind of Web requirements for which there partially exist a solution implemented by the Web site owner, but still users need to change or augment that implementation with very specific purposes that they desire to be available in such site. In this paper, we propose an approach for defining and evolving Web Augmentation requirements using rich visual prototypes and textual descriptions that can be automatically mapped onto running software artefacts. We present a tool implemented to support this approach and we show an evaluation of both the approach and the tool.
Formato de archivo PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
Requirements Engineering, 23(1), pp. 33-61.
Keywords: INGENIERÍA DE REQUERIMIENTOS; APLICACIONES WEB